СОЦИАЛЬНЫЙ СТАТУС ТРУДОВОГО МИГРАНТА В ЧУЖОЙ СТРАНЕ И ПРОБЛЕМА РАДИКАЛИЗАЦИИ - Саида Арифханова; Султанова Лилия (World Science, 2018)
Extremism is one of the most real contemporary threats to the national security of any country. Combating extremism involves understanding the factors and conditions of its occurrence. The solution of this problem from the standpoint of preventing of the emergence of extremist manifestations is related in the need of considering the various types of extremism. As a matter of fact, the process of recruitment and radicalization also takes places among the Central Asian immigrants in Russia. The youth, unskilled labor migrants, criminals and ethnic minorities are the potential recruits.